Effectiveness of simultaneous bilateral visual diaphragm biofeedback under low back pain: influence of age and sex - Molina-Hernández, Nerea; Rodríguez-Sanz, David; Chicharro, José López; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; Vicente-Campos, Davinia; Marugán-Rubio, Daniel; Gutiérrez-Torre, Samuel Eloy; Calvo-Lobo, César (Frontiers in Physiology, 2024)
The aim of the present study was to determine the effectiveness of simultaneous bilateral visual diaphragm biofeedback (BFB+IMT) by ultrasonography in conjunction with inspiratory muscle training (IMT) on diaphragmatic thickness during normal breathing, respiratory and clinical outcomes in patients with non-specific low back pain (NSLBP), and determine the age and sex influence. A single-blinded randomized clinical trial was carried out (NCT04582812). A total sample of 96 patients with NSLBP was recruited and randomized by based-sex stratification into IMT (n=48) and BFB+IMT (n=48) interventions during 8 weeks. Bilateral diaphragmatic thickness at maximum inspiration (T ins ) and expiration (T exp ), respiratory pressures, lung function, pain intensity, bilateral pressure pain threshold (PPT), disability, and quality of life were measured at baseline and after 8 weeks. The BFB+IMT group showed significant differences (P<0.05) with increased left hemi-diaphragm thickness at T ins and T ins-exp (d=0.38-053), and right and left PPT (d=0.71-0.74) versus the IMT group. The interaction with sex was statistically significant (P=0.007; F (1,81) =7.756; η p 2 =0.087) and higher left hemi-diaphragm thickness at T ins was predicted by the BFB+IMT group (R 2 =0.099; β=0.050; F (1,82) =8.997; P=0.004) and male sex (R 2 =0.079; β=0.045;F (1,81) =7.756;P=0.007). Also, greater left hemi-diaphragm thickness at T ins-exp was predicted by younger age (R 2 =0.052; β=-0.001; F (1,82) =4.540; P=0.036). The simultaneous bilateral visual diaphragm biofeedback by ultrasonography in conjunction with IMT was effective increasing the left diaphragmatic thickness during inspiration, which was positively influenced and predicted by male sex and younger age, and increasing the bilateral PPT of the paraspinal muscles in patients who suffered from NSLBP.